Nutritional status of high yielding crossbred cow around parturition (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The objective of this study was to evaluate nutritional status of high yielding dairy cattle around parturition.Materials and methods:  Nutritional status of cows around the peri-parturient period was investigated for six months in dairy farm. Seven to eight months pregnant cows were selected for this study. Blood samples from 24 randomly selected cows were collected at stage-1, -2 and -3. The serum was stored at -20ºC until analyzing glucose, total protein (TP), albumin (Alb), triglycerides (Tg), cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), calcium (Ca), magnesium (Mg) and phosphorus (P). Results: An increasing trend of glucose level was evidenced (P=0.07) during stage-1.  Instead, higher levels of TP were found during stage-3 as compared to the stage-1 and -2. The Alb levels differed significantly (P